2009
DOI: 10.1186/1423-0127-16-102
|View full text |Cite
|
Sign up to set email alerts
|

Blood haemoglobin measurement as a predictive indicator for the progression of HIV/AIDS in resource-limited setting

Abstract: BackgroundAnaemia is a frequent complication of infection with the human immunodeficiency virus (HIV) and may have multiple causes. The objective of this study was to find out if blood haemoglobin measurement could be used as an indicator for the progression of HIV/AIDS in resource-limited setting.MethodsTwo hundred and twenty-eight (228) consented People Living with HIV/AIDS (PLWHAs) who were placed in three groups according to their CD4 counts were used in the study. The three groups were those with CD4 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
60
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 38 publications
(36 reference statements)
17
60
1
7
Order By: Relevance
“…Current study results showed a small significant correlation of Hb to CD4 count which correlated well with several studies in Africa (Obirikorang and Yeboah, 2009;Owiredu et al, 2011;Wisaksana et al, 2011). In this study, a cut-off point of 10 g/dl had very low sensitivity.…”
Section: Markersupporting
confidence: 74%
See 1 more Smart Citation
“…Current study results showed a small significant correlation of Hb to CD4 count which correlated well with several studies in Africa (Obirikorang and Yeboah, 2009;Owiredu et al, 2011;Wisaksana et al, 2011). In this study, a cut-off point of 10 g/dl had very low sensitivity.…”
Section: Markersupporting
confidence: 74%
“…There was no correlation observed between RBC indices (MCH, MCHC and MCV) in this study. In contrast, in two different studies of RBC parameters and HIV, there was a significant decrease in RBC, RBC indices MCV and MCH (Obirikorang and Yeboah, 2009;Tagoe and Asantewaa, 2011). The results of this study exhibited no correlation of platelets to CD4 counts.…”
Section: Markermentioning
confidence: 96%
“…progression and death in individuals with HIV (4,11,(20)(21)(22)(23)(24). It is not clear why anemia is associated with risk of HIV progression, although it is unlikely that it has a direct effect.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify and monitor patients at risk of disease progression in resource-poor settings, the prognostic significance of various surrogate markers has been investigated (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Researchers have proposed many alternative markers, including hemoglobin (Hb) (6)(7)(8)(9)(10)(11), total lymphocyte count (TLC) (7,14,15), delayed-type hypersensitivity responses (5), serum albumin levels (13), neopterin (16), and body mass index (17). Due to the general availability of complete blood cell count (CBC) tests, particularly in resource-poor setting areas, this study investigated the prognostic value of CBC markers in HIV progression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, anemia frequently complicates HIV infection, is associated with faster progression, and is an independent risk factor for mortality. [14][15][16][17] In addition, anemic HIV-infected patients are more likely to require hospitalization or transfusion from a hemolytic crisis.…”
mentioning
confidence: 99%